2011
DOI: 10.1002/lary.21390
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and interventional sialendoscopy: A preliminary experience

Abstract: Sialendoscopy is safe and effective in managing non-neoplastic salivary gland disorders with low rates of major complications. Knowledge of options to navigate the rate-limiting steps, like dilation of the papilla and careful case selection, are key to successful outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 12 publications
(11 reference statements)
3
46
1
3
Order By: Relevance
“…While safe, the effectiveness of sialendoscopy may be limited by successful cannulation of the duct papilla. Reported rates of successful endoscope entry range from 96 to 98% [20]. The inability to cannulate 1 patient (4%) in this series is in agreement with these reported frequencies.…”
Section: Discussionsupporting
confidence: 81%
“…While safe, the effectiveness of sialendoscopy may be limited by successful cannulation of the duct papilla. Reported rates of successful endoscope entry range from 96 to 98% [20]. The inability to cannulate 1 patient (4%) in this series is in agreement with these reported frequencies.…”
Section: Discussionsupporting
confidence: 81%
“…For example, in the study of Koch et al,18 patients all had stenoses of different degrees and, although the overall success rate was low (22%), it varied widely depending on the type of stenosis, with 60% in type 1, 47% in type 2, and only 5% in type 3. Bowen et al 19 reported a success rate of 29% because most of the stones had a mean diameter of 8.2 mm and a combined approach technique was required to remove them. Finally, according to Gillespie et al,20 possible reasons for the lower success rate in their study (33%) could be a mean stone size near the upper limits of what can be easily extracted by endoscopy (7 mm), a lack of experience with endoscopic extraction techniques, a high rate of associated strictures, and a lack of access to lithotripsy or endoscopic laser.…”
Section: Discussionmentioning
confidence: 98%
“…This effect is likely due to the parotid gland consisting mostly of serous cells, which are more prone to injury from RAI treatment (19). Traditional methods of treating nonneoplastic disorders of the salivary glands are conservative treatment or salivary gland excision (20).…”
Section: Discussionmentioning
confidence: 99%